A meritocracia imbricada na dimensão subjetiva do mercado de trabalho formal - Abrantes, Cristina Gonçalves de (2021)
This work aimed to characterize meritocracy intertwined with the subjective dimension of the formal labor market. This goal was formulated based on the understanding that contemporary Brazilian society, that is grounded on neoliberal capitalism tends to relate to meritocracy as a premise to good social functioning. However, meritocracy as an ideology is fraught with contradictions and gaps that cannot be sustained. Demystifying it in a labor market constituent and also constituted by social inequality justifies the existence of this research. The theoretical and methodological framework of this research was Socio-Historical Psychology, which is based on historical and dialectical materialism. Different types of virtual media were analyzed, and recruiters responsible for the selection processes of private institutions were interviewed. It was persued a dialectical understanding of the subjective dimension of formal work, in which both the promotion of meritocratic practices, as well as submission to them happens. The analysis showed that the several changes that have occurred in the past few decades in the formal labor market do reveal the primary opposition between capital and labor, concerning their material and ideological aspects. The same occurs with the reinforcement of social inequality, placed in our material and symbolic context. In this scenario, meritocracy has at its core the purpose of protecting bourgeois values and acting in the maintenance of the instituted ones, and therefore it bears the illusory idea that the subject's success is directly proportional to their merit. These aspects characterize the subjective dimension of the recruitment and selection process in the formal labor market. It was found that the material bases and the ideal aspects of society are closely related, so that one dimension does not exist without the other, and both operate in benefit of the same destiny. In the case of capitalist societies, that destiny is the maintenance of social inequality. In this sense, meritocracy seems to be unattainable in the capitalist system, for one sustains the other. Pointing this codependency is key to the confrontation and overcoming of these contradictions